Investigating the impacts of avatar gender, avatar age, and region theme on avatar physical activity in the virtual world. (March 2017) - Zhang, Yulei (Gavin); Dang, Yan (Mandy); Brown, Susan A.; Chen, Hsinchun
Abstract: This study proposed a research model to examine the impacts of avatar gender, avatar age, and location (region theme) on avatars' physical activity. Each construct was measured at two levels: male and female for avatar gender, young and old for avatar age, commercial transaction and help-supporting for region theme, and high-active and low-active for avatar physical activity. The model was tested on Second Life, one of the most popular virtual worlds. An advanced data collection technique was created and applied to gather large-scale behavior data from real virtual-world residents in Second Life. To test the model and hypotheses, both the main effects and detailed interaction effects of the three factors were analyzed. Overall, the data analysis results indicated that in general male avatars were more physically active than female avatars, young avatars were more physically active than old avatars, and avatars in commercial transaction regions (for buying and selling virtual goods) were more physically active than avatars in help-supporting regions (for seeking or offering help). Highlights: Impacts of avatar gender, age, and region theme on physical activity were examined. Large-scale data from real virtual-world residents in Second Life were collected. In general, male avatars were more physically active than female avatars. In general, young avatars were more physically active than old avatars. Avatars were more physically active in shopping-related than help-related regions.